The FEA and experimental stress analysis in circular perforated plates loaded with concentrated force - Mateusz Konieczny; Grzegorz Gasiak; Henryk Achtelik (Fracture and Structural Integrity)
ABSTRACT. The paper presents an analysis of an isotropic circular axisymmetric perforated plate loaded with concentrated force Pi applied in the geometric center of the plate using finite element software ANSYS. The test plate with diameter D = 300 mm has holes in ten circles. The plate has holes with diameter d1 = 3.5 mm on the first inner circle, and holes on the tenth outside circle have a diameter d10 = 20.5 mm. The plate of the above geometry was free supported and loaded with different values of concentrated force. By means of numerical calculations using the finite element method, the coordinates of concentration zones of reduced stress in the perforated plate were determined. These zones were located on the plate bridges between perforation holes. The most hazardous place in the analyzed perforated plate is associated with the tenth zone Z10 with the hole radius d1 = 3.5 mm at the circle radius R1 = 22.5 mm, where the highest stress concentration occurs. In this zone, the reduced stress is σred max = 416.90 MPa (point with the coordinates x, y, z [mm], i.e. P10 [-69.9; 72.5; 0.0]). The results of numerical calculations were verified with experimental results. The differences between the results of numerical calculations of the state of stress and those obtained experimentally did not exceed 36%.